Supporting parents by combatting social inequalities in health: a realist evaluation - Annabelle Pierron; Laurence Fond-Harmant; François Alla (BMC, 2021)
Abstract Background To reduce social inequities in health, the World Health Organization's Commission on Social Determinants of Health recommends acting as soon as life begins. In this context, parenting support is promoted as a major lever. The objective of the present research was to develop an intervention theory establishing the conditions for the success of interventions, policies, and organizations supporting parenting in terms of reducing or preventing social inequalities in health for both mother and child in the perinatal period. Methods To meet these objectives, we conducted a realist evaluation based on a multiple-case study. The study evaluated two border towns in Europe. We collected data from three sources: documentary reviews, focus groups and interviews with professionals, and parental questionnaires. Results The main results concerning the fight against social inequalities in health show a true willingness on the part of those involved to carry out universal actions, coordinated between professionals and institutions, in response to the demands of parents; however, the reality on the ground shows the complexity of their implementation and the multiplicity of results. Our middle-range theory showed that to be effective in tackling social inequalities in health, actions must address structural determinants at the macro-systemic level. However, the field of realist evaluation shows that it is first and foremost the actions focused on individual behavior that are implemented. While there is a general political desire to combat social inequalities in health in early childhood, the results show that the strategies in place are potentially not the most effective. Effective support actions would respond to individual strategies; however, current approaches target parents' behavior, aiming to empower them but without giving them the means to do so. Conclusions This research constitutes a body of knowledge gathered for reflection and action. In particular, any perinatal policy should clearly state among its objectives the intention to reduce social inequalities in health. The policy should also state that it will be evaluated according to the criteria of proportionate universalism, interprofessional coordination, and actions based on the diversity of parents' needs.